2018
DOI: 10.1002/chem.201800745
|View full text |Cite
|
Sign up to set email alerts
|

APTRA‐Based Luminescent Lanthanide Complexes Displaying Enhanced Selectivity for Mg2+

Abstract: A series of three europium(III) complexes has been created in which an APTRA moiety has been integrated into the sensitising chromophore (APTRA=o-aminophenol-N,N,N-triacetate). The constitutionally isomeric complexes EuL and EuL feature the APTRA unit linked to a metal-bound pyridine ring through an alkynyl unit, differing according to the disposition of the APTRA substituents relative to the C≡C unit (para-N and para-O). In EuL , the APTRA ring is directly bonded to the Eu-coordinated pyridine (para-O). The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 34 publications
0
13
0
1
Order By: Relevance
“…Levy et al have previously demonstrated that bi-aryl systems containing an APTRA binding group display ar atiometric response to Mg 2 + andC a 2 + (L 5 ,F igure 1). [26,27] Ligand L 1 features an APTRAm oiety bound to a1 -naphthylalkynylf luorophore, and L 2 is constitutionally isomeric with L 1 , differing in the positiono ft he oxygen and nitrogen donor atoms aroundt he aromatic ring. [17] The developmento ft wo new phosphi-nate-based fluorescent indicators in particulari sd escribed, L 3 and L 4 ,a sa na lternative to the carboxylate-based APTRA binding chelate used in the literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Levy et al have previously demonstrated that bi-aryl systems containing an APTRA binding group display ar atiometric response to Mg 2 + andC a 2 + (L 5 ,F igure 1). [26,27] Ligand L 1 features an APTRAm oiety bound to a1 -naphthylalkynylf luorophore, and L 2 is constitutionally isomeric with L 1 , differing in the positiono ft he oxygen and nitrogen donor atoms aroundt he aromatic ring. [17] The developmento ft wo new phosphi-nate-based fluorescent indicators in particulari sd escribed, L 3 and L 4 ,a sa na lternative to the carboxylate-based APTRA binding chelate used in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…It also enabled the fluorescent systems to act as modelsf or lanthanide(III)-based complexes created in parallel work, to be reported elsewhere, in which pyridylalkynylaryl chromophores are also integratedt os ensitise lanthanide(III) emission efficiently. [26,27] Ligand L 1 features an APTRAm oiety bound to a1 -naphthylalkynylf luorophore, and L 2 is constitutionally isomeric with L 1 , differing in the positiono ft he oxygen and nitrogen donor atoms aroundt he aromatic ring. Ligand L 3 is ap hosphinate analogue of L 1 ,containing apentadentate APDAP binding chelate.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, they lead to intensity enhancements of a factor of three or so, when exciting at the isosbestic wavelength. Thus, examples have been reported of the detection of millimolar potassium in aqueous samples of a Eu complex with a remote phenanthridine sensitiser, 103 of millimolar magnesium levels in calf serum with a pyridyl arylalkynyl Eu complex 104 and of zinc at the micromolar level with a terbium complex. 105 In each case, the lanthanide emission lifetime is not changed.…”
Section: Reversible Change Of Ligand Constitution: I Emmentioning
confidence: 99%
“…Small molecule-based uorescent probes are versatile tools which are frequently explored as metal sensors. [14][15][16] Although probes with novel structures or improved properties are routinely developed, it remains a very active research area. For example, two uorescent rotaxane probes have been recently identied in Goldup's group as a selective Zn 2+ and Pt 2+ sensor.…”
Section: Introductionmentioning
confidence: 99%